Endonuclease G depletion may improve efficiency of first generation adenovirus vector DNA replication in HeLa cells - Misic, V; El-Mogy, M; Haj-Ahmad, Y (Cellular and Molecular Biology, 2015)
First generation adenovirus (Ad5 Î”E1,E3) vectors are able to replicate their DNA in many tumour cells and can be used for oncotherapy. Highest rates of viral DNA replication occur in the G2/M transition of the cell cycle. In this study, we tried to increase the efficiency of Ad5 Î”E1,E3 DNA replication in the cervical carcinoma HeLa cells by using RNA interference (RNAi) to target endonuclease G (EndoG) whose depletion leads to an accumulation of cells in the G2/M transition. Targeting of EndoG by an shRNA encoded on an Ad5 Î”E1,E3 vector resulted in an early proliferation defect of cervical carcinoma HeLa cells. This effect coincided with enhanced DNA replication and encoded transgene expression of an Ad5 Î”E1,E3 vector. Applied in high concentrations, the EndoG-targeting Ad5 Î”E1,E3 vector showed enhanced HeLa cell killing ability relative to control Ad5 Î”E1,E3 vectors. These effects are most likely the result of EndoG depletion, which causes cells to accumulate in the G2/M transition of the cell cycle and extends favourable cellular conditions for Ad5 Î”E1,E3 DNA replication. Targeting of EndoG by RNAi may be a viable strategy for improving both the levels of transgene expression and the oncolytic properties of first generation adenovirus vectors.